Hydrotherapy for labor and postpartum pain relief - Moshkebid M (Iran University of Medical Sciences, 1994)
Everybody knows water as a vital material for human being. Using water as a relaxation material which cause muscle smoothing and comfortable have been considered from long before. People of past centuries went to the thermal springs and immersed into them. Today groups of people go to seaside for swimming in their vacation. Children and adults go to pools for swimming or take a warm shower after a hard long day. Today in general, hydrotherapy has been verified by all. Before 1960s few had thought of labor in water. But first in 1960s Igor Tjarkovsky from Soviet :::union::: brought this thought into action and then Michel Odent from west introduced this method for the first time.